2021
DOI: 10.1038/s41467-021-25363-3
|View full text |Cite
|
Sign up to set email alerts
|

The antidepressant drug vilazodone is an allosteric inhibitor of the serotonin transporter

Abstract: Depression is a common mental disorder. The standard medical treatment is the selective serotonin reuptake inhibitors (SSRIs). All characterized SSRIs are competitive inhibitors of the serotonin transporter (SERT). A non-competitive inhibitor may produce a more favorable therapeutic profile. Vilazodone is an antidepressant with limited information on its molecular interactions with SERT. Here we use molecular pharmacology and cryo-EM structural elucidation to characterize vilazodone binding to SERT. We find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 104 publications
2
65
1
Order By: Relevance
“…To validate binding of 5-HT at the allosteric 5-HT site, we performed competition-binding experiments using [ 3 H]vilazodone ([ 3 H]VLZ), a recently developed and widely prescribed antidepressant predicted to bind to the allosteric site ( 17 ). We initially carried out saturation binding experiments in the presence of imipramine, which binds to the central site at nanomolar concentrations ( 16 ), and recorded a dissociation constant ( K d ) of 306 ± 36 nM for [ 3 H]VLZ (fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To validate binding of 5-HT at the allosteric 5-HT site, we performed competition-binding experiments using [ 3 H]vilazodone ([ 3 H]VLZ), a recently developed and widely prescribed antidepressant predicted to bind to the allosteric site ( 17 ). We initially carried out saturation binding experiments in the presence of imipramine, which binds to the central site at nanomolar concentrations ( 16 ), and recorded a dissociation constant ( K d ) of 306 ± 36 nM for [ 3 H]VLZ (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the existence and location of the allosteric binding site, and our understanding of allosteric regulation in NSS transporters, is incomplete ( 8 , 18 22 ). Before the studies reported here, extensive structural studies of NSS family members have only revealed inhibitors or detergent molecules bound within the extracellular vestibule ( 8 , 17 , 38 ). Here, we provide structural insight into how 5-HT occupies an allosteric site in SERT, demonstrating that this second substrate site is near, but not completely overlapping with, the previously described allosteric antidepressant binding site ( 8 , 35 , 36 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the primary binding site in dDAT GAT that carries 10 GAT1‐like substitutions, the extracellular vestibule was left largely unaltered and a single substitution was done in EL4 (E384S). Allosteric sites modulating neurotransmitter transport have gained prominence in the recent past with the identification of citalopram, vilazodone binding in hSERT at the allosteric site in the vestibule (Coleman et al , 2016; Plenge et al , 2021). Diverse interactions of noncompetitive inhibitors were also mapped in GlyTs with cmpd1 interacting with an inward‐open state and bioactive lipids proposed to interact with GlyT2 (Mostyn et al , 2019; Shahsavar et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These studies agree on a central orthosteric site, S1, that binds the substrate DA and competitive inhibitors/substrates such as cocaine and amphetamine (APMH) (Aggarwal et al, 2021;. Some studies have also suggested the existence of allosteric sites in the extracellular vestibule of DAT (Aggarwal & Mortensen, 2017;Navratna et al, 2018;Zhen & Reith, 2016), in the related serotonin transporter (Chen et al, 2005;Coleman et al, 2016b;Niello et al, 2020;Plenge et al, 2020Plenge et al, , 2021, and in the bacterial homologue LeuT (Beuming et al, 2008;Cheng & Bahar, 2013;Shan et al, 2011;Shi et al, 2008;Zhao et al, 2011). We have previously used structure/function studies to identify one allosteric site that we termed A2 (Aggarwal et al, 2019(Aggarwal et al, , 2021Kortagere et al, 2013).…”
Section: Significance Statementmentioning
confidence: 71%